2009
DOI: 10.1016/j.ygyno.2008.11.037
|View full text |Cite
|
Sign up to set email alerts
|

Trends in laparoscopic and robotic surgery among gynecologic oncologists: A survey update

Abstract: Objectives To assess the use of traditional and robotic assisted laparoscopy by Society of Gynecologic Oncology (SGO) members and to compare the results with those of our published survey in 2004. Methods Surveys were mailed to SGO members, and anonymous responses were collected by mail or through a web site. Data were analyzed and compared with those of our previous survey. In addition, we gathered information on the effect of robotic assisted surgery on the management of gynecologic malignancies. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
0
5

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(63 citation statements)
references
References 23 publications
2
56
0
5
Order By: Relevance
“…This allows for more easily identi fi able pelvic anatomy while patients experience decreased postoperative morbidity and faster recovery to permit rapid initiation of adjuvant radiotherapy or chemotherapy. The safety pro fi le of the da Vinci utilized for gynecologic oncology applications appears reassuring, with less blood loss and a low complication rate in managing ovarian, endometrial, and cervical cancers, respectively [38][39][40] .…”
Section: Clinical Applications In Gynecologic Oncologymentioning
confidence: 99%
“…This allows for more easily identi fi able pelvic anatomy while patients experience decreased postoperative morbidity and faster recovery to permit rapid initiation of adjuvant radiotherapy or chemotherapy. The safety pro fi le of the da Vinci utilized for gynecologic oncology applications appears reassuring, with less blood loss and a low complication rate in managing ovarian, endometrial, and cervical cancers, respectively [38][39][40] .…”
Section: Clinical Applications In Gynecologic Oncologymentioning
confidence: 99%
“…[29][30][31][32][33] However, a recent survey investigating the use of MIS by the Society of Gynecologic Oncology (SGO) members showed that only 26% of SGO members considered laparoscopic radical hysterectomy as an appropriate approach to the management of cervical cancer. 34 The Korean Gynecologic Oncology Group (KGOG) Survey also revealed that only 49% of KGOG members used laparoscopy for endometrial cancer staging surgery. 35 The potential obstacles to the widespread acceptance of minimally invasive approach in gynecologic cancer are the technical difficulties of conventional laparoscopic surgery.…”
Section: Robot Assisted Laparoscopic Surgery In Gynecologic Cancermentioning
confidence: 99%
“…Mots clé s : Chirurgie mini-invasiveCoelioscopie robot-assisté e -Cancer du col uté rin -Cancer de l'endomè tre Introduction Depuis plus de 20 ans, la chirurgie coelioscopique a pris une place croissante en chirurgie gyné cologique oncologique [12]. Ses avantages par rapport à la chirurgie ouverte sont maintenant reconnus, ré duisant les pertes sanguines, les douleurs postopé ratoires, la duré e d'hospitalisation et la convalescence, associé s à un pré judice esthé tique moindre.…”
Section: Robot-assisted Laparoscopy In Gynoncologic Surgery: What's New?unclassified